Model Pengembangan Kompetensi ASN dalam Transformasi Layanan Pajak Digital: : Studi Kasus Aplikasi ePonti di Kota Pontianak - Fahlevi, Ervin; Johannes, Ayu Widowati; Haeranah, Haeranah; Alwany, Taufan; Fahlevi, Rizky ramadan (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2025)
Digital transformation in the public service sector requires readiness and capacity building of State Civil Apparatus (ASN) in managing technology-based services effectively. This study aims to develop a relevant and applicable ASN competency development model to support the implementation of the ePonti application at the Pontianak City Regional Revenue Agency (Bapenda). This application is a digital innovation designed to facilitate online regional tax services. This study uses a qualitative descriptive approach with data collection techniques through in-depth interviews, direct observation, and documentation. Informants consisted of Bapenda employees and community service users. The results of the study showed a gap in employee competency in three main dimensions: technical competency, digital communication skills, and training effectiveness. Around 70% of employees have mastered basic features such as tax data input and validation, but only 30% understand advanced features such as analytical dashboards and automatic reporting. As many as 50% of employees have not been able to deliver technical education effectively to the public. The training provided is still general in nature, not based on job needs analysis, and has not reached all employees evenly. This study presents a competency development model based on technical integration, digital public communication, and adaptive training. This model also recommends a peer-assisted learning approach to enhance collaboration between employees and support the ongoing digital transformation of public services.